2022
DOI: 10.1093/conphys/coac074
|View full text |Cite
|
Sign up to set email alerts
|

The upper thermal limit of epaulette sharks (Hemiscyllium ocellatum) is conserved across three life history stages, sex and body size

Abstract: Owing to climate change, most notably the increasing frequency of marine heatwaves and long-term ocean warming, better elucidating the upper thermal limits of marine fishes is important for predicting the future of species and populations. The critical thermal maximum (CTmax), or the highest temperature a species can tolerate, is a physiological metric that is used to establish upper thermal limits. Among marine organisms, this metric is commonly assessed in bony fishes but less so in other taxonomic groups, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
(100 reference statements)
0
7
0
Order By: Relevance
“…Thermal tolerance mechanisms in elasmobranch fishes are poorly understood. To date, eight studies have quantified CT max in seven species of elasmobranch fishes: (i) four tropical species: the epaulette shark (Hemiscyllium ocellatum; Gervais et al, 2018;Wheeler et al, 2022), ribbontail stingray (Taeniura lymma; Dabruzzi et al, 2013), blacktip reef shark (Carcharhinus melanopterus; Bouyoucos et al, 2020Bouyoucos et al, , 2021 and sicklefin lemon shark (Negaprion acutidens; Bouyoucos et al, 2021); and (ii) three temperate species: the Atlantic stingray (Hypanus sabinus; Fangue and Bennett, 2003), Port Jackson shark (Heterodontus portusjacksoni; Gervais et al, 2021) and chain catshark (Scyliorhinus rotifer; Lupton and Bennett, 2023). These studies predominantly tested for effects of temperature acclimation on CT max without testing underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal tolerance mechanisms in elasmobranch fishes are poorly understood. To date, eight studies have quantified CT max in seven species of elasmobranch fishes: (i) four tropical species: the epaulette shark (Hemiscyllium ocellatum; Gervais et al, 2018;Wheeler et al, 2022), ribbontail stingray (Taeniura lymma; Dabruzzi et al, 2013), blacktip reef shark (Carcharhinus melanopterus; Bouyoucos et al, 2020Bouyoucos et al, , 2021 and sicklefin lemon shark (Negaprion acutidens; Bouyoucos et al, 2021); and (ii) three temperate species: the Atlantic stingray (Hypanus sabinus; Fangue and Bennett, 2003), Port Jackson shark (Heterodontus portusjacksoni; Gervais et al, 2021) and chain catshark (Scyliorhinus rotifer; Lupton and Bennett, 2023). These studies predominantly tested for effects of temperature acclimation on CT max without testing underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the captive epaulette sharks, data were also collected from wild sharks during catch and release sampling. Epaulette sharks were sampled at Balgal Beach, QLD ( n = 12; −19.021387, 146.418124) from May to June in 2021 and 2022 and on the Heron Island reef flat, QLD ( n = 60; −23.444622, 151.914889) from October to November 2021 (Wheeler et al ., 2022). Sharks were caught and measured in the same manner as described above.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the captive epaulette sharks, data were also collected from wild sharks during catch and release sampling. October to November 2021 (Wheeler et al, 2022). Sharks were caught and measured in the same manner as described above.…”
Section: Field Samplingmentioning
confidence: 99%
“…A meta-analysis by Bell et al (2009) found that several behavioural traits that were repeatable often differed among age classes, across sexes (also reported in O' Donnell et al 2020) and between field and laboratory studies. Many factors can elicit plasticity (variation) in CT max estimates, including differences in life stages (e.g., Illing et al, 2020;Recsetar et al, 2012), diet (Isaza et al, 2019), water quality (e.g., Ern et al, 2016;Potts, 2020;Sardella et al, 2008), habitat (Rodgers et al, 2019), reproductive stage (Auer et al, 2021;Dahlke et al 2020;Johnson, 1976;Wheeler et al, 2022) and social status (Gilmour & Bard, 2022;LeBlanc et al, 2011). Chronic stress in fish can also impair responses to thermal stress (e.g., Gilmour & Bard, 2022;Claireaux et al, 2013;LeBlanc et al, 2011).…”
Section: Is Ct Max Repeatable and What Does That Tell Us About Herita...mentioning
confidence: 99%